An Examination of Within- and Between-Family Influences on the Intergenerational Transmission of Violence and Maltreatment - Valgardson, Bradon A. (Journal of contemporary criminal justice, 2019)
Using a sample of sibling pairs from the National Survey of Adolescent to Adult Health (Add Health), the relationship between child and adolescent maltreatment and intimate partner violence (IPV) perpetration was examined within a genetically sensitive framework. After accounting for within-family similarities, maltreatment during childhood did not predict IPV. Maltreatment in adolescence, however, predicted increases in the likelihood of threatening an intimate partner as well as a combined measure of IPV. These results indicate that maltreatment represents only a single facet of the larger suite of family-level influences that contribute to the development of IPV perpetration.